Trypanosomosis: potential driver of selection in African cattle - Smetko, Anamarija; Soudre, Albert; Silbermayr, Katja; Müller, Simone; Brem, Gottfried; Hanotte, Olivier; Boettcher, Paul J.; Stella, Alessandra; Mészáros, Gábor; Wurzinger, Maria; Curik, Ino; Müller, Mathias; et al. (Frontiers in Genetics, 2015)
Trypanosomosis is a serious cause of reduction in productivity of cattle in tsetse-fly infested areas. Baoule and other local Taurine cattle breeds in Burkina Faso are trypanotolerant. Zebuine cattle, which are also kept there are susceptible to trypanosomosis but bigger in body size. Farmers have continuously been intercrossing Baoule and Zebu animals to increase production and disease tolerance. The aim of this study was to compare levels of zebuine and taurine admixture in genomic regions potentially involved in trypanotolerance with background admixture of composites to identify differences in allelic frequencies of tolerant and non tolerant animals. The study was conducted on 214 animals (90 Baoule, 90 Zebu and 34 composites), genotyped with 25 microsatellites across the genome and with 155 SNPs in 23 candidate regions. Degrees of admixture of composites were analyzed for microsatellite and SNP data separately. Average Baoule admixture based on microsatellites across the genomes of the Baoule-Zebu composites was 0.31, which was smaller than the average Baoule admixture in the trypanosomosis candidate regions of 0.37 (P=0.15). Fixation index FST measured in the overall genome based on microsatellites or with SNPs from candidate regions indicates strong differentiation between breeds. Nine out of 23 regions had FST ≥ 0.20 calculated from haplotypes or individual SNPs. The levels of admixture were significantly different from background admixture, as revealed by microsatellite data, for six out of the nine regions. Five out of the six regions showed an excess of Baoule ancestry. Information about best levels of breed composition would be useful for future breeding activities, aiming at trypanotolerant animals with higher productive capacity.